Uji Daya Hasil Lanjutan Galur Padi Harapan Tahan Tungro - Khaerana Khaerana; M Haiqal (xxxx-xxxx, 2023)
Khaerana K, Haiqal M. 2022. Advanced yield test of rice lines that are hopeful of tungro resistance. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 704-711.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Tungro is one of the important diseases in rice plants. Tungro disease in Indonesia has infected crops on a large scale in the 1960s. This disease causes a decrease in crop production by up to 80%, it can even cause puso. Line testing is one of the stages of the long process of creating a variety. The advanced yield test is the final stage of testing a line before the multi-location test is carried out. The purpose of this study was to select tungro-resistant promising rice lines that have high yield potential. In this study, there were 9 test lines used, with the comparison variety Mekongga, which were designed using a Randomized Block Design (RAK) with 3 replications. The results showed that the parameters of panicle number, panicle filled grain, panicle empty grain, and dry milled grain production were not significantly different between the comparison varieties and the nine lines tested. The comparison varieties showed that the plant height, weight of 1000 seeds and panicle length were significantly higher than the test lines. There were no test lines that showed better performance than the comparison variety, Mekongga.